Depletion of m6A reader protein YTHDC1 induces dilated cardiomyopathy by abnormal splicing of Titin. Issue 23 (30th October 2021) - Gao, Siyun; Sun, Haifeng; Chen, Kejing; Gu, Xueying; Chen, Hongyu; Jiang, Liudan; Chen, Lei; Zhang, Shengqi; Liu, Yi; Shi, Dan; Liang, Dandan; Xu, Liang; et al.
Abstract: N 6 ‐methyladenosine (m 6 A) is the most prevalent modification in mRNA and engages in multiple biological processes. Previous studies indicated that m 6 A methyltransferase METTL3 ('writer') and demethylase FTO ('eraser') play critical roles in heart‐related disease. However, in the heart, the function of m 6 A 'reader', such as YTH (YT521‐B homology) domain‐containing proteins remains unclear. Here, we report that the defect in YTHDC1 but not other YTH family members contributes to dilated cardiomyopathy (DCM) in mice. Cardiac‐specific conditional Ythdc1 knockout led to obvious left ventricular chamber enlargement and severe systolic dysfunction. YTHDC1 deficiency also resulted in the decrease of cardiomyocyte contractility and disordered sarcomere arrangement. By means of integrating multiple high‐throughput sequence technologies, including m 6 A‐MeRIP, RIP‐seq and mRNA‐seq, we identified 42 transcripts as potential downstream targets of YTHDC1. Amongst them, we found that Titin mRNA was decorated with m 6 A modification and depletion of YTHDC1 resulted in aberrant splicing of Titin . Our study suggests that Ythdc1 plays crucial role in regulating the normal contractile function and the development of DCM. These findings clarify the essential role of m 6 A reader in cardiac biofunction and provide a novel potential target for the treatment of DCM.